Performance of Microfinance Institutions: Does Government Ideology Matter?. (December 2017) - Gul, Ferdinand A.; Podder, Jyotirmoy; Shahriar, Abu Zafar M.
Highlights: Government ideology affects the performance of microfinance institutions (MFIs). In a left wing regime, MFIs have higher portfolio growth and lower annual expenses. MFIs operating in a left wing regime generate lower levels of financial revenue. The influence of government ideology is stronger among not-for-profit MFIs. Summary: We draw on the political economy theory and examine whether incumbent government's political ideology affects the performance of microfinance institutions (MFIs). We collect data on 619 MFIs from 75 countries over the period of 1996–2012 and merge them with country-level data on government ideology and other economic and institutional factors. We find that MFIs operating in a left wing regime have higher portfolio growth rates relative to the ones operating in a right wing or a centrist regime. Furthermore, under leftist political leadership, MFIs have lower funding costs, lower operating costs, and lower default costs. The electoral incentives of left wing governments, however, impair the capacity of MFIs to increase financial revenue. Thus, despite having lower costs, these MFIs are not more sustainable relative to those operating in right wing or centrist regimes. Academics and policymakers devote substantial resources to better understand the conditions under which MFIs are more likely to flourish and deliver on their promises. We contribute to this endeavor by empirically showing that government ideology is an important determinant of MFI performance.